Efficacy of Transurethral Bladder Neck Incision with 2-Micron Continuous Wave Laser (RevoLix) for the Management of Bladder Outlet Stricture in Women - Sharifiaghdas, Farzaneh; Kardoust Parizi, Mehdi; Ahadi, Babak (Urology Journal, 2013)